A case of EBUS-TBNA in a Total Laryngectomy Patient using High Flow Nasal Oxygen - Nehme, Ralph (Archives of Clinical and Medical Case Reports, 2023)
Endobronchial Ultrasound transbronchial needle aspiration (EBUSTBNA) is currently considered as the gold standard technique for the assessment of mediastinal, hilar and centrally located lymph nodes and tumours. However, the ideal approach to sedation and oxygen supplementation during the procedure has not been clearly defined especially in particular clinical scenarios like total laryngectomy patients. In the following article we present the case of an EBUS-TBNA in a total laryngectomy patient done under moderate sedation and oxygenation using a heated High Flow Nasal Oxygen canula. The purpose of this case report is to shed light on the feasibility of the procedure under moderate sedation and the utility of the HFNO in special patients as those having a total laryngectomy.